(untitled) (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
The translations were created by third-year students of the Scandinavian Studies program, who show a particular interest in Scandinavian literatures, the complete works of Knut Hamsun, and other Scandinavian authors.